1997
DOI: 10.1103/physreva.55.265
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic model for quantum scattering: Reformulation, analysis, and numerical strategies

Abstract: The convergence problem for scattering states is studied in detail within the framework of the Algebraic Model, a representation of the Schrödinger equation in an L 2 basis. The dynamical equations of this model are reformulated featuring new "Dynamical Coefficients", which explicitly reveal the potential effects. A general analysis of the Dynamical Coefficients leads to an optimal basis yielding well converging, precise and stable results. A set of strategies for solving the equations for non-optimal bases is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…It was shown that an acceptable precision for light p-shell nuclei can be achieved with 30-50 oscillator functions [10,13,46]. In some model situations this number can be further reduced, even down to 3 or 5 functions, as was shown in [47]. The calculation of matrix elements of different operators between oscillator functions can be done with the technique of the Generalized Coherent States [10,48,49], which leads to recurrence relations for the matrix elements.…”
Section: Model Space and Hamiltonianmentioning
confidence: 98%
“…It was shown that an acceptable precision for light p-shell nuclei can be achieved with 30-50 oscillator functions [10,13,46]. In some model situations this number can be further reduced, even down to 3 or 5 functions, as was shown in [47]. The calculation of matrix elements of different operators between oscillator functions can be done with the technique of the Generalized Coherent States [10,48,49], which leads to recurrence relations for the matrix elements.…”
Section: Model Space and Hamiltonianmentioning
confidence: 98%
“…It was conjectured (see for instance [20]) that for very large values of the oscillator quantum number n the expansion coefficients for physically relevant wave-functions behave like…”
Section: B Asymptotic Solutions In Oscillator Representationmentioning
confidence: 99%
“…It dramatically improves the convergence of the results with significantly smaller values for N . We refer to [20] for further details.…”
Section: Numerical Solution and Convergencementioning
confidence: 99%
See 2 more Smart Citations